PKCδ Deficiency Perturbs Bone Homeostasis by Selective Uncoupling of Cathepsin K Secretion and Ruffled Border Formation in Osteoclasts - Cremasco, Viviana (2012)
Bone homeostasis requires stringent regulation of osteoclasts, which secrete proteolytic enzymes to degrade the bone matrix. Despite recent progress in understanding how bone resorption occurs, the mechanisms regulating osteoclast secretion, and in particular the trafficking route of cathepsin K vesicles, remain elusive. Using a genetic approach, we describe the requirement for PKCδ in regulating bone resorption by affecting cathepsin K exocytosis. Importantly, PKCδ deficiency does not perturb formation of the ruffled border or trafficking of lysosomal vesicles containing the v-ATPase. Mechanistically, we find that cathepsin K exocytosis is controlled by PKCδ through modulation of the actin bundling protein MARCKS. The relevance of our finding is emphasized in vivo as PKCδ−/− mice exhibit increased bone mass and are protected from pathological bone loss in a model of experimental post-menopausal osteoporosis. Collectively, our data provide novel mechanistic insights into the pathways that selectively promote secretion of cathepsin K lysosomes independently of ruffled border formation, providing evidence for the presence of multiple mechanisms that regulate lysosomal exocytosis in osteoclasts.